2009
DOI: 10.1128/jvi.01700-08
|View full text |Cite
|
Sign up to set email alerts
|

Small Molecule Targets Env for Endoplasmic Reticulum-Associated Protein Degradation and Inhibits Human Immunodeficiency Virus Type 1 Propagation

Abstract: Human immunodeficiency virus type 1 (HIV-1) is dependent on its envelope glycoprotein (Env) to bind, fuse, and subsequently infect a cell. We show here that treatment of HIV-1-infected cells with glycyl-prolyl-glycine amide (GPG-NH 2 ), dramatically reduced the infectivity of the released viral particles by decreasing their Env incorporation. The mechanism of GPG-NH 2 was uncovered by examining Env expression and maturation in treated cells. GPG-NH 2 treatment was found to affect Env by significantly decreasin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 34 publications
0
14
0
Order By: Relevance
“…The resulting pellet containing the membrane fraction was resuspended with reducing Laemmli sample buffer and the supernatant containing the soluble fraction was precipitated with 20% TCA before dissolving in sample buffer. Endoglycosidase H (Endo-H) and peptide-n-glycosidase F (PNGase F) treatments were performed on 20 l of transfected cell post-nuclear supernatants according to the manufacturer's instructions (New England Biolabs) except that 5% SDS was used in place of 10ϫ glycoprotein denaturing buffer (32).…”
Section: Methodsmentioning
confidence: 99%
“…The resulting pellet containing the membrane fraction was resuspended with reducing Laemmli sample buffer and the supernatant containing the soluble fraction was precipitated with 20% TCA before dissolving in sample buffer. Endoglycosidase H (Endo-H) and peptide-n-glycosidase F (PNGase F) treatments were performed on 20 l of transfected cell post-nuclear supernatants according to the manufacturer's instructions (New England Biolabs) except that 5% SDS was used in place of 10ϫ glycoprotein denaturing buffer (32).…”
Section: Methodsmentioning
confidence: 99%
“…Further electron microscopy studies indicated a possible interaction of GPG‐NH 2 derivatives with viral capsid assembly [16]. We have also shown that αHGA has an effect on HIV‐1 envelope precursor protein, gp160, through the endoplasmic reticulum associated protein degradation pathway [17,18]. Thus, this compound affects two steps in the virus replication cycle.…”
Section: Introductionmentioning
confidence: 77%
“…Proteins targeted by ERAD are partially deglycosylated, exported out the ER, and targeted for degradation in a proteasome dependent manner (reviewed in 7173. It has been previously demonstrated that treatment of Env expressing cells with GPG-NH 2 causes Env to undergo ERAD, which results in gp160 migrating at a molecular weight (MW) similar to wild type gp120 due to gp160 partial deglycosylation [67,74]. If a population of gp160 was partially deglycosylated via ERAD, it could affect the identification and quantitation of the gp160 and gp120 levels in the Ubc9 knockdown cells.…”
Section: Resultsmentioning
confidence: 99%
“…Activation of the unfolded protein response was analyzed by XBP-I splicing as previously described with slight modifications [67]. Briefly, transfected and untransfected 293T cells were treated with 5mM dithiothreitol (DTT) for 3 hours or left untreated.…”
Section: Methodsmentioning
confidence: 99%